Pore channel functionalized covalent organic framework catalyst for CO2 reduction reaction and preparation method thereof

By introducing the organometallic complex 1,1'-diborate into the covalent organic framework material TFp-BPy, the pore functional catalyst DBFc@TFp-BPy, the problem of low catalytic activity of existing COFs materials is solved. , achieving more efficient CO2 reduction reaction performance.

CN119411166APending Publication Date: 2025-02-11ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411569795.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing metal-coordinated covalent organic framework (COFs) materials have low catalytic activity in the electrocatalytic field, limiting their application in CO2 reduction reactions.

Method used

The pore functionalized covalent organic frame catalyst DBFc@TFp-BPy is formed by introducing the organometallic complex 1,1'-diborate into the pores of the covalent organic frame material TFp-BPy.

Benefits of technology

The structural stability and electrocatalytic performance of the catalyst are improved, and the activity and selectivity of CO2 reduction reaction are significantly improved. In particular, the reduction of Tafel slope indicates stronger electrocatalytic activation ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411166A_ABST
    Figure CN119411166A_ABST
Patent Text Reader

Abstract

The invention relates to a pore channel functionalized covalent organic framework catalyst for CO2 reduction reaction, which is of a composite framework structure DBFc (at) TFp-BPy formed by taking a covalent organic framework material TFp-BPy as a framework and introducing and limiting an organic metal complex 1, 1 '-ferrocene diborate into a pore channel of the TFp-BPy by utilizing the internal and external pressure difference of pores of the TFp-BPy. According to the invention, an organic metal complex 1, 1 '-ferrocene diborate is introduced into a pore channel of a TFp-BPy frame material to prepare a novel composite frame structure with excellent structural stability and good electrocatalytic activity, and the composite frame structure can be used as a catalyst in an electrochemical CO2 reduction reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and relates to a catalyst for a carbon dioxide reduction reaction, and in particular to a pore functionalized catalyst based on a covalent organic framework structure and a preparation method thereof. Background Art

[0002] With the development of industrialization and urbanization, the burning of fossil fuels continues to increase, and excessive CO2 emissions cause global warming, which is not conducive to my country's low-carbon transformation and development. Electrochemical CO2 reduction technology has the advantages of high efficiency and energy saving, environmental friendliness, product diversification and high technical maturity, and has broad application prospects in the field of CO2 conversion.

[0003] The CO2 reduction reaction (CO2RR) electrolyzer can solve the problem of excessive CO2 emissions during fossil fuel combustion and industrial development. As the core component of the CO2RR electrolyzer, the catalyst plays a vital role in the electrochemical CO2RR (eCO2RR), and its performance directly affects the efficiency and selectivity of the eCO2RR.

[0004] An ideal catalyst should have high activity, high selectivity, good stability, excellent conductivity, cost-effectiveness, scalability and environmental friendliness. Current research focuses on developing various types of catalysts such as metal catalysts, metal oxides, metal sulfides, metal organic frameworks (MOFs) and covalent organic frameworks (COFs), and optimizing performance by adjusting their composition and structure. With the continuous progress of research, innovative catalyst design will provide key support for the commercialization of eCO2RR technology and addressing the challenges of global climate change.

[0005] COFs as catalysts show significant advantages in eCO2RR, mainly reflected in their highly ordered porous network structure, adjustable porosity and functionality, excellent thermal and chemical stability, molecular design, improved conductivity, synergistic catalytic effect, and high activity and selectivity. These characteristics enable COFs to provide more active sites, optimize the adsorption and activation of CO2, and improve catalytic efficiency while maintaining long-term operational stability. In addition, the environmental friendliness of COFs makes it a powerful tool for reducing greenhouse gas emissions and promoting sustainable energy conversion. Therefore, COFs have great application potential and development prospects as catalysts in eCO2RR.

[0006] Although COFs materials have made a lot of progress in the field of electrocatalysis, there are still some problems to be solved. For example, COFs materials without metal coordination lack active sites, resulting in low catalytic activity, which restricts their development in the field of catalysis. It is of great significance to improve the catalytic performance of COFs materials by modifying the pores of metal sites through impregnation.

[0007] Soumitra Payra et al. (Structure-Sensitive Electrocatalytic Reduction ofCO2 to Methanol over Carbon-Supported Intermetallic PtZn Nano-Alloys[J]. ACS Appl. Mater. interfaces, 2020, 04, 16.) reported for the first time the catalytic effect of carbon-supported PtZn nanoalloys on CO2RR, and synthesized PtZn / C, Pt3Zn / C and Pt x Zn / C (1<x<3) catalysts, and their reaction mechanisms and kinetics were elucidated by experiments and density functional theory (DFT) calculations. All of them showed good catalytic performance, among which Pt x Zn / C is the best performing catalyst with a Tafel slope of 587 mv dec. -1 .

[0008] Although Pt-based catalysts have shown good performance, their electrochemically active surface area is low, which limits the efficiency of their catalytic reactions and leads to low catalytic activity. In addition, Pt-based catalysts contain precious metal elements, which are expensive and will result in high preparation costs and resource pressure. Summary of the invention

[0009] The purpose of the present invention is to provide a novel pore-functionalized covalent organic framework catalyst and a preparation method thereof, which is used for electrochemical CO2 reduction reaction and has both excellent structural stability and good catalytic activity.

[0010] The pore-functionalized covalent organic framework catalyst of the present invention uses the covalent organic framework material TFp-BPy as a framework, and introduces the organic metal complex 1,1'-diboronodifluorocene into the pores of TFp-BPy to form a composite framework structure DBFc@TFp-BPy having a structure shown in the following structural formula (I):

[0011] Among them, OMCs is the abbreviation of organometallic complex 1,1'-ferrocene diboronate.

[0012] Specifically, the organometallic complex 1,1'-ferrocene diboronate has a structure shown in the following structural formula (II):

[0013] The pore-functionalized covalent organic framework catalyst of the present invention is obtained by confining the organic metal complex 1,1'-ferrocene diborate in the pores of the TFp-BPy framework by utilizing the pressure difference between the inside and outside of the pores of the framework. The catalyst is an orange-red powder and is insoluble in organic solvents.

[0014] Furthermore, in the pore-functionalized covalent organic framework catalyst of the present invention, the mass ratio of the TFp-BPy framework to 1,1'-ferrocene diborate is 1:5-200.

[0015] Furthermore, the mass ratio of the TFp-BPy framework to 1,1'-ferrocene diborate is more preferably 1:100-150.

[0016] On the other hand, the present invention also provides a method for preparing the pore-functionalized covalent organic framework catalyst, specifically, the covalent organic framework material TFp-BPy is preheated at 90 to 100° C. under a vacuum state, and then a methanol-water mixed solution of the organic metal complex 1,1'-ferrocene diboronate is injected, and negative pressure impregnation is performed under a vacuum state to allow the 1,1'-ferrocene diboronate to be fully immersed in the pores of TFp-BPy, and after drying, a composite framework structure shown in structural formula (I) is formed.

[0017] Furthermore, in the mixed solution for dissolving 1,1'-ferrocene diborate, the volume ratio of methanol to water is preferably 3:1 to 1.5.

[0018] Wherein, the preheating treatment is carried out in a continuous vacuum environment, and the preheating treatment time is preferably 24 to 30 hours.

[0019] Furthermore, the negative pressure impregnation is carried out at 40-60° C., and the negative pressure impregnation time is preferably 30-48 hours.

[0020] It should be noted that the vacuum environment described in the present invention is not a complete vacuum environment, but a continuous negative pressure environment obtained by intermittent vacuuming by a vacuum pump.

[0021] In order to facilitate negative pressure impregnation of the covalent organic framework material TFp-BPy, the present invention also preferably performs ultrasonic crushing treatment on the TFp-BPy, specifically, the covalent organic framework material TFp-BPy is dispersed in a dimethylformamide or N-methylpyrrolidone solvent system to form a suspension, and the suspension is crushed at low temperature using an ultrasonic cell crusher, and the solvent is removed to obtain a refined TFp-BPy material. The refined TFp-BPy material is more conducive to subsequent pore modification.

[0022] More specifically, the present invention preferably uses an ultrasonic cell disruptor with a power of 200 to 300 W to disrupt the suspension at a low temperature of 0 to 30° C., and the preferred disruption treatment time is 1.5 to 3 hours.

[0023] Furthermore, the TFp-BPy used as the framework in the present invention may be TFp-BPy prepared by various reported preparation methods, and the present invention has no particular limitation thereto.

[0024] However, preferably, the TFp-BPy described in the present invention can be a TFp-BPy framework structure obtained by condensing trialdehyde pyrogallol and 5,5'-diamino-2,2'-bipyridine as raw materials in an N,N-dimethylaniline / 1,2-dichlorobenzene solvent system in an acetic acid aqueous solution.

[0025] Specifically, the molar ratio of trialdehyde phloroglucinol to 5,5'-diamino-2,2'-bipyridine is preferably 1:1.5-2.

[0026] The present invention successfully prepared a new composite framework structure DBFc@TFp-BPy with excellent structural stability and electrocatalytic performance by introducing an organic metal complex 1,1'-diboronoquinoline containing catalytic sites into the pores of the TFp-BPy framework material. The DBFc@TFp-BPy can be used as a catalyst for electrochemical CO2 reduction reactions.

[0027] The present invention peels off the multi-layer nanostructured TFp-BPy into a single-layer nanostructure, and confines the organometallic complex 1,1'-diboronoferrocene in the pores of TFp-BPy by negative pressure impregnation, and designs and constructs the nano-impregnated "ferrocene" COFs structure catalyst DBFc@TFp-BPy. Compared with the unmodified TFp-BPy, the uniformity of active site distribution, electrical conductivity and reaction catalytic activity are improved. In addition, compared with other existing related framework structures, the basic electrocatalytic performance of the catalyst has also been greatly improved, especially the Tafel slope is significantly reduced, showing a stronger electrocatalytic activation ability.

[0028] The preparation method of the pore impregnation modified DBFc@TFp-BPy composite framework structure of the present invention is simple, the production cost is low, it is easy to scale up production, and it shows broad application potential in multiple fields such as gas separation and catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the X-ray photoelectron spectroscopy (XPS) comparison diagram of DBFc@TFp-BPy and TFp-BPy.

[0030] Figure 2 This is a comparison chart of infrared spectra (FTIR) of DBFc@TFp-BPy and TFp-BPy.

[0031] Figure 3 are scanning electron microscope (SEM) images of DBFc@TFp-BPy and TFp-BPy.

[0032] Figure 4 are the transmission electron microscopy (TEM) images of DBFc@TFp-BPy and TFp-BPy.

[0033] Figure 5 This is the linear sweep voltammetry (LSV) comparison curve between DBFc@TFp-BPy and TFp-BPy.

[0034] Figure 6 This is a comparison graph of the Tafel slopes of DBFc@TFp-BPy and TFp-BPy.

[0035] Figure 7 It is the cyclic voltammetry (CV) curve of TFp-BPy.

[0036] Figure 8 This is the cyclic voltammetry (CV) curve of DBFc@TFp-BPy.

[0037] Fig. 9 This is a comparison curve of the double-layer capacitance of DBFc@TFp-BPy and TFp-BPy. Implementation

[0038] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0039] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0040] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example

[0041] Example 1

[0042] Trialdehyde phloroglucinol (208 mg, 1 mmol) and 5,5'-diamino-2,2'-bipyridine (279 mg, 1.5 mmol) were dissolved in 20 ml of N,N-dimethylaniline / 1,2-dichlorobenzene mixed solution (1:1 v / v), placed in a 50 ml Teflon-lined autoclave, and ultrasonicated for 5 min to make it uniformly dispersed. Then, 2.7 ml of 6 mol L -1 The mixture was stirred with a magnetic stirrer for 2 h, sealed, and heated to 120 °C for 72 h.

[0043] The precipitate was collected by centrifugation, washed with anhydrous tetrahydrofuran (6×4 ml) and acetone (3×4 ml), respectively, and dried under vacuum at 80°C overnight to obtain orange-red TFp-Bpy with a yield of 65%.

[0044] Example 2

[0045] The TFp-Bpy prepared in Example 1 was ground into powder and dispersed in 50 ml of dimethylformamide solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. An ultrasonic cell disruptor was used to disrupt the suspension for 1.5 hours at a power of 200 W. During this period, the ultrasonic on / off time was set to 2s and 3s respectively.

[0046] The suspension was vacuum filtered, washed with methanol (15×3 ml), and dried overnight at 80°C in vacuum to obtain a finer orange-red TFp-Bpy powder.

[0047] Weigh 30 mg of the above-mentioned dried TFp-Bpy powder into a reaction bottle and evacuate for 2 minutes. Repeat the operation three times or more, then heat the reaction bottle to 90°C in an oil bath for 30 hours, during which time the evacuation is repeated every 2 hours.

[0048] Weigh 1,1'-ferrocene diborate (0.41 g, 1.5 mmol) and dissolve it in a mixed solution of 10 ml of anhydrous methanol and 3.5 ml of deionized water to prepare an impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 36 h.

[0049] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean petri dish, and dried overnight under vacuum at 80 °C to obtain a deep red product DBFc@TFp-BPy with a yield of 85%.

[0050] Example 3

[0051] The TFp-BPy prepared in Example 1 was ground into powder and dispersed in 50 ml of dimethylformamide solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. An ultrasonic cell disruptor was used to disrupt the suspension at a power of 200 W for 1.5 h, during which the ultrasonic on / off time was set to 2 s and 3 s respectively.

[0052] The suspension was vacuum filtered, washed with methanol (15 × 3 ml), and dried overnight at 80 °C in vacuum to obtain a finer orange-red TFp-BPy powder.

[0053] Weigh 30 mg of the above-mentioned dried TFp-BPy powder into a reaction bottle and evacuate the solution for 2 min. Repeat the operation three times or more. Then, heat the reaction bottle to 95°C in an oil bath for 24 h, during which the evacuation is repeated every 2 h.

[0054] Weigh 1,1'-ferrocene diborate (4.10 g, 15 mmol) and dissolve it in a mixed solution of 15 ml of anhydrous methanol and 5 ml of deionized water to prepare an impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 30 h.

[0055] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean petri dish, and dried overnight under vacuum at 80 °C to obtain a deep red product DBFc@TFp-BPy with a yield of 65%.

[0056] Example 4

[0057] The TFp-BPy prepared in Example 1 was ground into powder and dispersed in 50 ml of dimethylformamide solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. An ultrasonic cell disruptor was used to disrupt the suspension at a power of 200 W for 1.5 h, during which the ultrasonic on / off time was set to 2 s and 3 s respectively.

[0058] The suspension was vacuum filtered, washed with methanol (15 × 3 ml), and dried overnight at 80 °C in vacuum to obtain a finer orange-red TFp-BPy powder.

[0059] Weigh 30 mg of the above-mentioned dried TFp-BPy powder into a reaction bottle and evacuate the solution for 2 min. Repeat the operation three times or more. Then, heat the reaction bottle to 90°C in an oil bath for 30 h, during which the evacuation is repeated every 2 h.

[0060] Weigh 1,1'-ferrocene diborate (6.02 g, 22 mmol) and dissolve it in a mixed solution of 20 ml of anhydrous methanol and 10 ml of deionized water to prepare an impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 36 h.

[0061] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight under vacuum at 80 °C to obtain a deep red product DBFc@TFp-BPy with a yield of 60%.

[0062] Example 5

[0063] The TFp-Bpy prepared in Example 1 was ground into powder and dispersed in 50 ml of N-methylpyrrolidone solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. An ultrasonic cell disruptor was used to disrupt the suspension for 3 h at a power of 200 W, during which the ultrasonic on / off time was set to 2 s and 2 s respectively.

[0064] The suspension was vacuum filtered, washed with methanol (15 × 3 ml), and dried overnight at 80 °C in vacuum to obtain a finer orange-red TFp-BPy powder.

[0065] Weigh 30 mg of the above-mentioned dried TFp-BPy powder into a reaction bottle and evacuate for 2 minutes. Repeat the operation three times or more, and then heat the reaction bottle to 100°C in an oil bath for 24 hours, during which the evacuation is repeated every 2 hours.

[0066] Weigh 1,1'-ferrocene diborate (4.10 g, 15 mmol) and dissolve it in a mixed solution of 20 ml of anhydrous methanol and 10 ml of deionized water to prepare an impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 40°C for 48 h.

[0067] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean petri dish, and dried overnight under vacuum at 80 °C to obtain a deep red product DBFc@TFp-BPy with a yield of 70%.

[0068] Example 6

[0069] The TFp-BPy prepared in Example 1 was ground into powder and dispersed in 50 ml of N-methylpyrrolidone solvent to form a suspension. The suspension temperature was kept at 0°C by circulating cooling. The suspension was crushed for 3 h using an ultrasonic cell disruptor at a power of 150 W, during which the ultrasonic on / off time was set to 2 s and 2 s respectively.

[0070] The suspension was vacuum filtered, washed with methanol (15 × 3 ml), and dried overnight at 80 °C in vacuum to obtain a finer orange-red TFp-BPy powder.

[0071] Weigh 30 mg of the above-mentioned dried TFp-BPy powder into a reaction bottle and evacuate for 2 minutes. Repeat the operation three times or more, and then heat the reaction bottle to 100°C in an oil bath for 24 hours, during which the evacuation is repeated every 2 hours.

[0072] Weigh 1,1'-ferrocene diborate (4.10 g, 15 mmol) and dissolve it in a mixed solution of 20 ml of anhydrous methanol and 10 ml of deionized water to prepare an impregnation reagent, which is slowly injected into the reaction bottle using a disposable syringe and reacted at 60°C for 30 h.

[0073] The reaction product was separated, washed with methanol (15 × 3 ml), placed on a clean Petri dish, and dried overnight under vacuum at 80 °C to obtain a deep red product DBFc@TFp-BPy with a yield of 72%.

[0074] Application Example 1

[0075] 10 mg of TFp-BPy powder was weighed and dispersed in a mixed solution of 5 wt % Nafion (50 μL) solution and ethanol (950 μL), and ultrasonically treated until a uniform dispersed phase was formed.

[0076] Cut the hydrophobic carbon paper into 1×1 cm size, set the pipette range to 20 μL, and evenly apply 100 μL of the above mixed solution on the surface of the carbon paper in five times.

[0077] Weigh the mass of carbon paper before and after the addition, and calculate the catalyst loading to be 1 mg cm -2 .

[0078] The carbon paper coated with the catalyst was placed in a vacuum oven and dried at 60°C for 6 h to prepare the TFp-BPy working electrode.

[0079] Application Example 2

[0080] 10 mg of the DBFc@TFp-BPy powder of Example 3 was weighed and dispersed in a mixed solution of 5 wt % Nafion (50 μL) solution and ethanol (950 μL), and ultrasonically treated until a uniform dispersed phase was formed.

[0081] Cut the hydrophobic carbon paper into 1×1 cm size, set the pipette range to 20 μL, and evenly apply 100 μL of the above mixed solution on the surface of the carbon paper in five times.

[0082] Weigh the mass of carbon paper before and after the addition, and calculate the catalyst loading to be 1 mg cm -2 .

[0083] The carbon paper coated with the catalyst was placed in a vacuum oven and dried at 60°C for 6 h to prepare the DBFc@TFp-BPy working electrode.

[0084] Application Example 3

[0085] The basic structure characterization of the TFP-BPy catalyst and DBFc@TFp-BPy catalyst loaded on the hydrophobic carbon paper prepared in the above-mentioned application examples 1 and 2 was carried out. The results are as follows: Figures 1 to 4 shown.

[0086] XPS is a characterization method based on the principle of photoelectric effect. When the surface of a material is irradiated by X-rays, the X-ray photons interact with the atoms on the surface of the material and excite the electrons on the surface of the material to a higher energy level. By analyzing the energy and number of these excited electrons, we can know the chemical composition, chemical state and spatial distribution of elements on the surface of the material. Figure 1 Compared with the electronic energy spectrum of TFP-BPy, the Fe 2p Peak and B 1s The peaks demonstrated the successful introduction of 1,1'-ferrocene diboronate.

[0087] Fourier transform infrared spectroscopy (FTIR) can be used to effectively identify the structure of substances. Figure 2 The FTIR analysis results showed that 3094cm -1 The CH stretching vibration peak on the cyclopentadienyl ring; 1197cm -1 It is the B-OH vibration peak on the cyclopentadienyl ring; 784cm -1 The out-of-plane deformation vibration peak of CH on the cyclopentadienyl ring; 475cm -1 The results further confirmed that 1,1'-ferrocene diborate was successfully impregnated into the pores of TFP-BPy.

[0088] Figure 3 The SEM analysis results show that the organic metal complex is attached to the surface of the modified DBFc@TFp-BPy in the left picture, and compared with the right picture, it can be seen that its morphology is hardly destroyed during the pore functionalization modification process.

[0089] Figure 4The TEM analysis results show that the spherical clusters of the original TFP-BPy in the right image are hollow, however, due to the introduction of the complex, the TEM image of DBFc@TFp-BPy in the left image becomes darker than TFP-BPy, confirming the presence of the organic metal complex in the pores.

[0090] Application Example 4

[0091] Furthermore, the electrochemical performance tests of the TFP-BPy catalyst and DBFc@TFp-BPy catalyst loaded on the hydrophobic carbon paper prepared in the above-mentioned application examples 1 and 2 were also carried out. The results are as follows: Figures 5 to 9 .

[0092] All electrochemical tests were performed on a standard three-electrode cell system of the LVIUMSTAT electrochemical workstation. The reaction vessel used for the test was an H-type electrolyzer, the electrolyte was a 0.5 mol / L KHCO3 solution, and the catalyst was used as the working electrode (working electrode area 1 mg cm -2 ), a 1×1 cm platinum sheet was used as the counter electrode, and a mercury oxide (Hg / HgO) electrode was used as the reference electrode (the reference electrode was calibrated before use). The electrochemical properties of the prepared catalysts, such as LSV, CV, and Tafel, were tested, and the CO2RR performance of the catalysts at room temperature was evaluated.

[0093] The DBFc@TFp-BPy catalyst and TFp-BPy catalyst were subjected to LSV tests in Ar atmosphere and CO2 atmosphere, respectively. Figure 5 The LSV (linear sweep voltammetry) curve for evaluating CO2RR activity is shown in the figure. In the potential range of -0.8 to -1.2 V vs. RHE, the current density of DBFc@TFp-BPy in CO2 atmosphere is much greater than that in Ar atmosphere, indicating that DBFc@TFp-BPy has good CO2RR activity; at the same time, in CO2 atmosphere, the current density of DBFc@TFp-BPy is also much greater than that of TFp-BPy, indicating that the CO2RR performance of DBFc@TFp-BPy is better than that of TFp-BPy.

[0094] In order to find out the source of the good performance of DBFc@TFp-BPy, the Tafel slope was used to explore its kinetic performance of CO2RR. The lower the Tafel slope value, the higher its electrocatalytic activity. This was used to compare the kinetic performance of DBFc@TFp-BPy and TFp-BPy. Figure 6 It can be seen from the Tafel diagram given that the Tafel slope of DBFc@TFp-BPy is 289mv dec. -1 , lower than TFp-BPy (422mv dec -1), indicating that DBFc@TFp-BPy has more effective charge transfer ability and larger active surface during the reaction, and this structure is more conducive to promoting the reaction kinetics.

[0095] Electrochemically active surface area (ECSA) is one of the methods to characterize the number of microscopic active sites of a catalyst. However, it is difficult to measure ECSA directly. The double layer capacitance C is generally used. dl Qualitative expression of ECSA, C dl The larger the value, the larger the ECSA and the more active sites. dl The measured values ​​were obtained by performing cyclic voltammetry (CV) tests at different scan rates in the non-Faraday current region.

[0096] At a scan rate of 10.0 mV s –1 , 30.0mV s –1 , 50.0mV s –1 , 70.0mV s –1 and 90.0mV s –1 TFp-BPy and DBFc@TFp-BPy were tested by CV respectively, and the results were Figure 7 , Figure 8 The CV curve shown. Take the absolute value of the current density difference at the intermediate potential ΔJ ,by ΔJ Plotted against the corresponding scan rate, the slope is the double layer capacitance C dl The larger the capacitance value, the more active sites there are per unit area, which is more conducive to the reduction reaction.

[0097] With the scanning speed as the horizontal axis, ΔJ Plot C for the ordinate dl Graphs (such as Fig. 9 As shown in Figure 2), it can be seen that the C dl The value is greater than that of TFp-BPy, so the ECSA of DBFc@TFp-BPy is greater than that of TFp-BPy. Due to the addition of 1,1'-diboronic acid ferrocene, DBFc@TFp-BPy has more active sites and thus has higher CO2RR catalytic activity.

[0098] These test results indicate that an appropriate amount of organometallic complex pore impregnation modification can provide more available active surface area for electrolyte penetration and improve the catalytic activity of the catalyst.

[0099] The above embodiments of the present invention do not describe all the details of the present invention in detail, nor do they limit the present invention to the above embodiments. Those skilled in the art may make various changes, modifications, substitutions and variations to these embodiments without departing from the principles and purpose of the present invention, which shall all be included in the protection scope of the present invention.

Claims

1. A pore-functionalized covalent organic framework catalyst for CO2 reduction reaction, which uses the covalent organic framework material TFp-BPy as the framework. The pressure difference between the inside and outside of the pores of the TFp-BPy framework is used to introduce the organic metal complex 1,1'-diboronodifluorocene into the pores of TFp-BPy to form a composite framework structure DBFc@TFp-BPy.

2. The pore-functionalized covalent organic framework catalyst for CO2 reduction reaction according to claim 1, wherein the mass ratio of the TFp-Bpy framework to 1,1'-ferrocene diboronate in the catalyst is 1:5-200.

3. The pore-functionalized covalent organic framework catalyst for CO2 reduction reaction according to claim 2, characterized in that The mass ratio of TFp-Bpy framework to 1,1'-ferrocene diboronate is 1:100-150.

4. The method for preparing the pore-functionalized covalent organic framework catalyst for CO2 reduction reaction according to claim 1 is to preheat the covalent organic framework material TFp-Bpy at 90-100°C under vacuum, inject a methanol-water mixed solution of the organic metal complex 1,1'-ferrocene diboronate, perform negative pressure impregnation under vacuum, so that 1,1'-ferrocene diboronate is fully immersed in the pores of TFp-Bpy, and form a composite framework structure after drying.

5. The preparation method according to claim 4, characterized in that The volume ratio of methanol to water in the mixed solution is 3:1-1.

5.

6. The preparation method according to claim 4, characterized in that Preheat treatment in a continuous vacuum environment for 24 to 30 hours.

7. The preparation method according to claim 4, characterized in that Immerse under negative pressure at 40-45°C for 30-48 hours.

8. The preparation method according to claim 4, characterized in that Before the preheating treatment, TFp-Bpy is dispersed in a dimethylformamide or N-methylpyrrolidone solvent system to form a suspension, and an ultrasonic cell disruptor is used to perform ultrasonic disruption treatment to remove the solvent to obtain a refined TFp-Bpy material.

9. The preparation method according to claim 8, characterized in that The suspension is disrupted for 1.5 to 3 hours using an ultrasonic cell disruptor with a power of 200 to 300 W at a low temperature of 0 to 30°C.

10. The pore-functionalized covalent organic framework catalyst according to claim 1 is used as a catalyst for electrochemical CO2 reduction reaction.